Tay-Sachs Disease: From Molecular Characterization to Ethical Quandaries and the Possibility of Genetic Medicine - Jessica, F. Smith; Jeffrey, O. Henderson (Journal of Neurological Research And Therapy, 2022)
Tay-Sachs disease (TSD) is a rare neurodegenerative disorder caused by mutations in the HEXA gene, which encodes the ɑ subunit of the enzyme β-hexosaminidase A. Lacking this key enzyme in GM2 ganglioside catabolism, individuals who are homozygous for HEXA mutations suffer from abnormal accumulation of GM2 ganglioside in brain and nerve cells, ultimately resulting in the progressive deterioration of the central nervous system. TSD is one of three disorders characterized by β-hexosaminidase deficiency; Sandhoff disease (SD) and the AB variant arise by mutations in the HEXB and GM2A genes respectively, which disrupt other points of GM2 ganglioside degradation. Characterized by developmental delay and stagnation, muscular weakness, coordination deficits, seizures, and eventual hearing and vision loss, these three disorders are clinically indistinguishable and occur in three forms defined by age of onset. While there is a much higher incidence of TSD in the Ashkenazi Jewish population, community carrier screening and counseling initiatives have reduced disease prevalence to about the equivalent of non-Jewish populations; however, such efforts have raised ethical concerns in the Jewish community that are increasingly relevant in light of scientific and medical advancements. Currently, treatments for TSD and its related disorders focus on symptom management, with gene therapies and the application of modified CRISPR-Cas-9 technology being explored.
Keywords: CRISPR-Cas-9; ganglioside; hexosaminidase; TSD; Sandhoff disease